Estudo sobre prognóstico nas afecções da medula espinhal em cão - Motta, Marco Aurélio Avendano (2023)
Spinal cord disorders in dogs can occur due to various causes such as neoplasia and intervertebral disc extrusion (IVDE). These diseases can affect different regions of the spinal cord, the prognosis of which may vary according to the degree of neurological dysfunction, type of disease, and in cases of neoplasia, the presence or absence of metastases. Article 1 of this thesis describes a case report of neoplasm of the anal sac with metastasis in the vertebral body, spinal cord, and cauda equina, as well as the unfavorable prognosis. Complementary imaging exams showed involvement of bone and nerve tissues, and alterations in lymph nodes suggesting metastasis. The histopathological examination concluded that it was a carcinoma of a type confirmed by immunohistochemistry, showing the importance of this examination in complementing the histopathological findings. The objective of Article 2 was to quantify the free DNA in the cerebrospinal fluid (CSF) and blood plasma and to use the concentration as a prognosis for the return to walking of paraplegic dogs due to IVDE (Hansen type I) and submitted to decompressive surgery. The 30 dogs were divided into three groups of equal number: Group I (control): healthy; Group II: with paraplegia and presence of deep pain perception (DPP); Group III: with paraplegia and absence of DPP. In dogs from Groups II and III, dorsolateral hemilaminectomy was performed together with the fenestration of the affected intervertebral disc. Group I was submitted to blood (plasma) and CSF collection for measurement of free DNA at day 0 (before surgery) and Groups II and III at day 0 and 30 and 90 days postoperative. In Group II, 100% of the dogs returned to walking satisfactorily. In Group III, 40% of the dogs had satisfactory recovery, 40% remained paraplegic (unsatisfactory), and 20% developed spinal gait. The concentration of free DNA in the CSF was higher in dogs from Groups II and III at day 0, demonstrating CSF free DNA to be more sensitive in detecting spinal cord injury than the levels found in plasma. The concentration of free DNA in the plasma and CSF of dogs from Groups II and III remained high at 30 and 90 days postoperative, despite the recovery of ambulation. In conclusion, it is possible to quantify free DNA in CSF and plasma, but the concentration should not be used as a biomarker in the prognosis for the return to walking of paraplegic dogs with or without DPP, caused by IVDE TL after surgery.